Bovine mixed leucocyte reactions and generation of cytotoxic cells - Goddeeris, Bruno M.; Lalor, P.A.; Morrison, W. Ivan (Cambridge University Press, 1986)
The inductive requirements for proliferation of bovine peripheral blood mononuclear cells (PMB) in vitro, in the allogeneic mixed leucocyte reation (MLR), the autologous MLR and the autologous Theileria MLR were compared. In order to examine the role of monocytes in these reactions, methods were developed to deplete PBM of monocytes as well as to obtain purified monocytes. Depletion of monocytes (to less than 0.2%)could be achieved reproducibly by harvesting PBM from defibrinated blood followed by incubation on plastic for 2 h. Monocytes of greater than 95% purity were obtained by sorting with a cell sorter using a monoclonal antibody specific for monocytes within PBM. It was found that monocytes were required in the stimulator population for induction of both the allogeneic and autologous MLR and that purified monocytes. Stimulator cells fixed with glutaraldehyde did not induce either an autologous or allogeneic MLR. Genetically restricted cytotoxic cells were generated in the allogeneic MLR but not in the autologous MLR. Monocytes were not required for proliferation in the autologous Theileria MLR. Furthermore, the response could be elicited using Theileria-infected cells fixed with glutaraldehyde. However, stimulation with fixed cells was dependent on the presence of monocytes in the responder population. Cytotoxic cells were generated in the autologous Theileria MLR: using PMB from immune animals, at least a proportion of the effector population generated in vitro killed in a MHC-restricted way.